Using quality-of-life indicators in rehabilitation program evaluation - Fabian, Ellen [Verfasser] (My University, 1991)
"This article discusses three measurement approaches to assessing quality of life for individuals with disabilities, provides examples of these approaches, and discusses implications for practical use of quality-of-life indicators in rehabilitation program evaluation." (author's abstract) ((en)) In dem Beitrag werden drei Ansätze zur Messung der Lebensqualität behinderter Menschen vorgestellt, Anwendungsbeispiele beschrieben und Möglichkeiten des praktischen Einsatzes der Lebensqualitätsindikatoren bei der Evaluation von Rehabilitationsprogrammen diskutiert. (IAB)
Die Benutzung von Indikatoren der Lebensqualität bei der Evaluation von Rehabilitationsprogrammen
Keywords: G 2.4.2 Lebenskonzepte, -stile, Werte; Menschen mit Behinderung; Lebensqualität; Messung; Rehabilitation; Erfolgskontrolle